Sulfate reduction and homoacetogenesis at various hypersaline conditions: Implications for H2 underground gas storage - Schwab, Laura; Prinsen, Lilian; Nowack, Guido; Popp, Denny; Noll, Matthias; Vogt, Carsten; Wagner, Martin (Frontiers in Energy Research, 2023)
While interest in underground gas storage (UGS) of hydrogen (H2) in salt caverns is increasing in a growing H2 economy, knowledge of the microbial communities inhabiting those hypersaline environments is still scarce. High salt concentrations and limited availability of carbon (C) sources in cavern environments reduce microbial growth rates and metabolic activities. Growth conditions potentially change once H2 is stored in salt caverns. H2 is a universal electron donor that can facilitate autotrophic growth and subsequently growth of heterotrophs. In this study, a mixed culture enriched from hypersaline UGS sites was investigated in microcosm experiments with H2 atmosphere, testing the effect of different salt concentrations and C sources on methanogenesis, sulfate reduction and homoacetogenesis. Sulfate, acetate and lactate concentrations were quantified throughout a time span of 125 days of incubation and correlations with the microbial community structure and function were explored through 16S rRNA gene-based amplicon sequencing at the end of the experiment. Many of the amplicon sequence variants (ASVs) were only assigned to family or order level, reflecting that a large number of ASVs belong to previously undescribed taxa. At 4.4 M NaCl, close to cavern brine salinity, members of the Desulfovibrionales were absent when no C source other than CO2 was offered as the sole C source. This is in line with the finding that no sulfate reduction occurred at these conditions. Acetogenic Halanaerobiia dominated in these high salinity levels. Based on metagenome sequencing of four selected samples, we found that acetogenesis at autotrophic conditions relies on the activity of a halophilic homoacetogen, Acetohalobium sp. and that sulfate reduction can most likely be associated with a so far undescribed member of the Desulfonatronovibrionales. We further discuss the discrepancy between sulfate reduction at heterotrophic conditions, while no sulfate reduction was observed under autotrophic conditions although acetate was produced through the homoacetogenic activity of Acetohalobium. For the application of UGS of H2, this means that the presence and activity of the aforementioned microorganisms must be investigated, as they can eventually lead to the formation of acetate and allow sulfate reduction at relevant concentrations.